A proposed calendar of topical book display ideas for primary schools in the Philippines - Calaor, Ronara E.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
The paper had two principal problems: (1) what is a calendar of topical book display ideas that can be utilized by primary schools in the Philippines? and (2) is book display an effective public relations technique for primary schools in the Philippines?
The researcher used the experimental method of research to answer the second problem. The researcher performed the experiment at the Grades 3-6 Library (experimental group) of the UP Integrated School (UPIS) while the Kindergarten-Grade 2 Library served as controlled group, not experiencing any treatment. The controlled group is a weak controlled group because the two libraries are located at different building, thus, not really being controlled. The pretest and posttest was performed for 21 school days. There were two three-dimensional put up one after the other for 19 days each. The researcher relied on the statistics gathered at the control desk of both libraries for her data gathering. The data gathered from the experiment was quantitatively analyzed and compared. The survey method of research was utilized for the first problem. The researcher's primary source for the book display ideas is the Department of Education Culture and Sports' (DECS) memoranda. She utilized the Filway's Philippine Almanac (1991) and the History of the Filipino people as cross-references and considered current issues and events as sources. The data gathered from the survey were arranged according to the date it is proposed to be put up.
From the experimental group, the researcher concluded that the average number of users for the three periods (pretest, treatment, and posttest) increased but she concluded that this was not due to the book display because there was also increase in the controlled group. The researcher further concluded that there was already a trend of increase on the number of users in both the libraries or group.
The researcher came up with a calendar of book display ideas to be utilized by primary schools in the Philippines through her analysis of the DECS memoranda and the current issues and events happening around the country and the world.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Elementary school libraries -- Philippines -- Activity programs; Library exhibits -- Philippines; Library exhibits -- Philippines